Factors that affecting employee performance in Block A and B Perbadanan Putrajaya / Adawiah Mohamad Tojid - Mohamad Tojid, Adawiah (Faculty of Business and Management, 2019)
Employee performance is important role in organization as it is a critical factor for organization success. In addition, unperformed employees will somehow impact the organization in order to achieve their targets and goals. Therefore, this study seeks to examine factors that can influence employee performance. This study focuses on several factors that can influence employee performance such as working environment, motivation and intrinsic reward. The objective of this study is to identify the factors that affecting employee performance in Perbadanan Putrajaya. The sampling technique that was used in this study is convenient sampling and the data collection was used is self-administered questionnaire. The researcher have distribute 288 questionnaire to 288 of the respondents, then get the return questionnaire of 208 of the respondents. The data that had been collected was then evaluated by using Statistical Package for the Social Science (SPSS) Software version 22. Then, using SPSS test that were converged such as reliability analysis, frequency analysis, descriptive analysis, Pearson’s correlation analysis and multiple regression. The results indicated from the factors which include working environment, motivation and intrinsic reward are related to employee performance. The findings of the study revealed that all independent variables were found to have significant relationships with dependent variable which is employee performance. However, based on the result it had been found that there are other independent variable that can influence employee performance which is not included in this study.